The dynamics of reading development in L2 English for academic purposes. (August 2021) - Gui, Min; Chen, Xiaokan; Verspoor, Marjolijn
Abstract: In a mixed-methods approach, this study investigates the complex and dynamic developmental trajectories of 27 Chinese Chemistry major undergraduates' English academic reading ability. Twelve parallel tests were designed, validated, and used weekly during one semester. The analyses included a group pre-post design to measure academic reading gains, a regression analysis to predict beginning reading score with English proficiency and Chemistry knowledge as predictors, individual longitudinal case studies to measure variability and phase shifts, and a cluster analysis to discover (un)common developmental patterns. Finally, a qualitative study used interviews to discover difficulties in reading and strategies to overcome them. English proficiency predicted the initial reading score and the group gained significantly in academic reading. Each learner showed different non-linear patterns, and a cluster analysis revealed few similar patterns among learners. The high gainers showed relatively more variability over time and used more and a wider variety and more sophisticated learning and reading strategies to improve.